Fact versus Fake: How Smart People are Losing Rationality during Infodemic - Azim, Syeda Saadia; Dey, Dipayan; Roy, Arindam (South Asian Journal of Social Sciences and Humanities, 2021)
The present study is an attempt to understand the propagation of health-related fake news in India during COVID-19 pandemic in diversely distributed WhatsApp groups comprising uneven groups of members. Ten different WhatsApp groups were selected covering demographic and socio-economic profile and ten most important health-related fake news were studied. Different fake news circulation paths like forward, react, multi-forward, reference etc. were analyzed for different groups. It was observed that older generations - boomers were more susceptible towards fake news and they tended to distribute the fake news in different groups. Male boomers actively circulate pseudo-science information whereas female boomers distribute faith-based information in the WhatsApp group. Levels of education, social media influence or ignorance, technology access, age, gender and understanding played a major role in the distribution and propagation of fake information during times of COVID. It can be also inferred that easy availability of data and devices, lack of understanding of the game of social media and unscientific baggage of age-old beliefs were some factors for over -dependence and reliance on fake news.